Revolutionizing Education with Interactive Tech Boosts Global Learning Outcomes: Merevolusi Pendidikan dengan Teknologi Interaktif Meningkatkan Hasil Pembelajaran Global - Jaxongirmirzo, Mamatisakov (Indonesian Journal of Innovation Studies, 2024)
This study explores the impact of innovative technologies—such as computer programs, mobile applications, interactive textbooks, 3D modeling, and virtual experiences—on enhancing learning and teaching processes. The research adopts a mixed-methods approach to analyze how these tools affect students' mastery and engagement across various educational disciplines. Preliminary results indicate that these technologies significantly improve comprehension of complex subjects and increase student engagement, particularly highlighting the effectiveness of interactive textbooks and online platforms in ensuring timely course completion. The findings suggest that integrating these modern methods into educational curricula can greatly enhance learning efficiency and outcomes, recommending further exploration into long-term effects and optimal implementation strategies. Highlights: Technologies like 3D modeling boost understanding of complex concepts. Tools such as apps enhance student participation and interest. Modern tech improves course completion and learning outcomes. Keywords: Educational Technology, 3D Modeling, Interactive Learning, Digital Tools, Animations